Cross linked Poly (4-Vinylpyridine-Ethylene Glycol Dimethacrylate) Used for Preconcentration of Cd(II) and its Determination by Flow Injection Flame Atomic Absorption Spectrometry - Teixeira Tarley, Cesar Ricardo; Botteon Farias, Natalia Cristina; Lima, Giovana de Fatima; Oliveira, Fernanda Midori de; Bonfilio, Rudy [UNESP]; Dragunski, Douglas Cardoso; Clausen, Debora Nobile; Segatelli, Mariana Gava (Aoac Int, 2014)
The main purpose of this research was to synthesize crosslinked poly(4-vinylpyridine-ethylene glycol dimethacrylate) and evaluate its feasibility for highly sensitive and selective determination of Cd in water samples by using flow injection flame atomic absorption spectrometry. The crosslinked polymer, prepared by bulk polymerization, was characterized by FTIR spectrometry and scanning electron microscopy. The flow injection solid-phase method was based on preconcentration of 20.0 mL of sample through 100 mg of the polymer packed into a minicolumn at pH 8.25 using a flow rate of 6.0 mL/min, followed by elution with 1.0 M HNO3. The sample solution parameters influencing the preconcentration behavior of Cd ions, such as pH, buffer concentration, and flow rate, were simultaneously studied and optimized using? Doehlert matrix. Values of 0.10 mu g/L, 2.0-210 mu g/L, 32.3, 18/h, 9.7/min, and 0.62 mL were obtained for LOD, linear range, preconcentration factor, sample throughput, concentration efficiency, and consumption index, respectively. The effect of the presence of the inorganic cations Pb(II), U(IV), Co(II), Hg(II), Cu(II), As(III), Mg(II), Sb(III), Ni(II), Th(IV), Ba(II), and Ca(II) on the method was studied, and the preconcentration of Cd was observed to have no interference. The accuracy of the method was assessed by analysis of natural water samples using addition and recovery tests and inductively coupled plasma/MS as a reference technique, as well as by analysis of a standard reference material of trace elements in water.